Tempos do passado e tempos do futuro em confronto: diferenças e paralelismos - Cunha, Luís Filipe (Revista da Associação Portuguesa de Linguística, 2021)
This paper deals with the main similarities and differences that arise between past and future tenses. In particular, we argue that, while the propositions associated with past tenses are completely settled and their truth-value can be evaluated at the speech time, the propositions described by future tenses cannot be seen as true or false at the utterance time since these linguistic forms are ramifying, in that they typically point to a variety of inertia histories or inertia worlds. Nevertheless, if we consider more closely some particular tenses in European Portuguese – namely the Pretérito Imperfeito (Imperfect) and the Pretérito Perfeito do Indicativo (simple past), as representatives of the past tenses, and the Futuro Simples (simple future) and the structure ir (‘go’) + Infinitive, as representatives of the future ones, we conclude that there are also some important parallels across the two temporal domains. We claim that both the Imperfeito and the Futuro Simples merely locate the situations in a past or future interval, respectively, and that the final interpretation of the sentences in which they occur is the result of the interaction of their temporal characteristics with aspectual and modal features. The Pretérito Perfeito and the structure ir (‘go’) + Infinitive, on the other hand, share the common property of imposing an additional temporal boundary beyond which the eventualities cannot take place; as a result, aspectual effects and modal readings are much more conditioned and pure temporal interpretations – both in the past and in the future – become greatly predominant.